Right coronary artery to coronary sinus fistula: $hBastian Schmack, Matthias Karck and Alexander Weymann - Schmack, Bastian; Karck, Matthias; Weymann, Alexander (Asian cardiovascular & thoracic annals, 2016)
Coronary fistulas are extremely rare. The right coronary artery is frequently involved but the coronary sinus, as a draining site, is fairly uncommon. We present a rare congenital coronary fistula of a giant right coronary artery in a 53-year-old female patient, which had a shunting volume of 3L min-1